2018
DOI: 10.1039/c8fo01140k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the anti-angiogenic potential of hydroxytyrosol and five derivatives

Abstract: Hydroxytyrosol is a phenolic compound present in extra virgin olive oil, either in free form or as derivatives, and related to some of the health benefits described for olive oil intake. We have demonstrated previously that hydroxytyrosol inhibits angiogenesis both in vitro and in vivo. In the present study, we evaluate the anti-angiogenic potential of five hydroxytyrosol derivatives. Three of these derivatives contain a nitro group and they exhibit a much weaker effect than hydroxytyrosol in the tubule format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
(70 reference statements)
3
13
0
Order By: Relevance
“…Their IC 50 values showed that only one of those compounds (Solo F–OH in the present work) had a relevant cytotoxic activity in the totality of cell lines tested at the low micromolar range [17]. The promising results reported for Solo F–OH, together with our ongoing interest in the discovery and characterization of new antiangiogenic compounds [24,25,26,27,28], prompted us to evaluate the antiangiogenic potential of the complete series of solomonamide precursors in a primary screening in vitro for the inhibition of endothelial tubular-like structures formation on Matrigel.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Their IC 50 values showed that only one of those compounds (Solo F–OH in the present work) had a relevant cytotoxic activity in the totality of cell lines tested at the low micromolar range [17]. The promising results reported for Solo F–OH, together with our ongoing interest in the discovery and characterization of new antiangiogenic compounds [24,25,26,27,28], prompted us to evaluate the antiangiogenic potential of the complete series of solomonamide precursors in a primary screening in vitro for the inhibition of endothelial tubular-like structures formation on Matrigel.…”
Section: Discussionmentioning
confidence: 83%
“…Attending to this evidence, the active search for new compounds that are able to modulate angiogenesis is a crucial research strategy in order to discover potential antiangiogenic drugs with possible clinical applications. Our group is actively involved in the identification and characterization of new natural bioactive compounds and synthetic derivatives with multitarget antiangiogenic effects [24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our previous results with HT, we proposed the idea that the structural modification of HT might improve its antiangiogenic activity, giving rise to new drug candidates for the treatment of diseases characterized by a deregulated angiogenesis. As part of a search program for HT derivatives with improved profiles, the antiangiogenic potential of five HT derivatives was recently evaluated by us (López-Jiménez, Gallardo, Espartero, Madrona, Quesada & Medina, 2018). Results showed that introduction of a nitro group in the HT ring was detrimental for its antiangiogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ex vivo (rat aortic ring) and in vivo (CAM) angiogenesis assays supported the antiangiogenic activity of hydroxytyrosol [66], which could be related to the inhibition of COX-2 and VEGFR-2 phosphorylation [61,67]. Recently, the antiangiogenic activity of synthetic molecules derived from hydroxytyrosol has been described, showing that chemical modifications in the original molecule may improve the bioactivity of the natural compound, therefore reinforcing their utility as angiopreventive compounds [68]. In contrast with the antiangiogenic activity described for hydroxytyrosol, the closely related compound tyrosol, also present in olive oil, did not show capability to inhibit angiogenesis in vitro [66].…”
Section: Olive Oil As a Source Of Antiangiogenic Moleculesmentioning
confidence: 99%